Blanco White and Walter Scott Blanco white y Walter Scott - Fernando DURÁN LÓPEZ (Cuadernos Dieciochistas, 2011)
The first edition of Ivanhoe; a romance. By the author of Waverley was published in Edinburgh in 1820. From the beginning of year 1823, José María Blanco White translated several excerpts from Ivanhoe in the numbers 1-3 of the magazine Variedades, owned by the publisher Rudolph Ackermann. in these articles and other later writings, the translator praised Scott as a model for a new way of painting history in a narrative. This paper studies his ideas on Scott’s historical novel, as well as his translation technique, compared with that of José Joaquín de Mora. En 1820 se publicó en Edimburgo la primera edición de Ivanhoe; a romance. By the author of Waverley. Desde comienzos de 1823, en los tres primeros números de su revista Variedades, promovida por el editor Rudolph Ackermann, José María Blanco White tradujo varios fragmentos de Ivanhoe entre grandes elogios. Asimismo, Blanco White tomó a Scott como modelo de referencia de una nueva manera de pintar la historia por medio de la novela en otros varios escritos críticos de años posteriores. El artículo estudia las ideas de Blanco White acerca de la novela histórica de Scott y su técnica como traductor, comparada con la de José Joaquín Mora.